2019
DOI: 10.1128/mmbr.00062-18
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Within-Host Microevolution of Mycobacterium tuberculosis through Whole-Genome Sequencing: the Phenotypic Impact and Way Forward

Abstract: SUMMARY The Mycobacterium tuberculosis genome is more heterogenous and less genetically stable within the host than previously thought. Currently, only limited data exist on the within-host microevolution, diversity, and genetic stability of M. tuberculosis. As a direct consequence, our ability to infer M. tuberculosis transmission chains and to understand the full complexity of drug resistance profiles in individual patients is limited. Furthermore, apart from the acquisition of certain drug resistance-confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 97 publications
(182 reference statements)
6
61
0
Order By: Relevance
“…The LPAs and Deeplex-MycTB provide direct information on the occurrence of RIF heteroresistance, whereas Ultra, after informing that RR was detected, may suggest RIF heteroresistance only through additional examination of wild-type and Mut melt probes and corresponding melt peak temperatures in the raw data on the computer screen or in the generated extended report (Supplemental File Figure S3 b-e, f). The clinical importance of heteroresistance is likely substantial (2), akin to ’fixed‘, i.e. 100% resistance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The LPAs and Deeplex-MycTB provide direct information on the occurrence of RIF heteroresistance, whereas Ultra, after informing that RR was detected, may suggest RIF heteroresistance only through additional examination of wild-type and Mut melt probes and corresponding melt peak temperatures in the raw data on the computer screen or in the generated extended report (Supplemental File Figure S3 b-e, f). The clinical importance of heteroresistance is likely substantial (2), akin to ’fixed‘, i.e. 100% resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings can thus inform and guide TB reference laboratory staff, healthcare providers, and researchers, that the threshold for reporting resistance in case of rifampicin heteroresistance is the highest for Classic Xpert and Ultra, to resolve phenotypic and genotypic discordant rifampicin-resistant TB results. Prospective large-scale clinical studies using next generation sequencing approaches (2, 7) are necessary to establish the proportion of mutants that predicts poor outcome of treatment with the specific drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from this, novel genetic variants may be fixed in the population by the mechanism of hitchhiking or independently [10]. A comprehensive review of these mutations has been recently published and demonstrated that most of these variants occurred in the genes, associated with the compensatory mechanisms, virulence, or relapse and survival, but their consequences remain unclear [11].…”
Section: Introductionmentioning
confidence: 99%